Smart Drug Delivery Strategies for Cancer Therapy - López Mendoza, Carlos Miguel; Alcántara Quintana, Luz Eugenia (Frontiers in Nanotechnology, 2022)
Chemotherapy is one of the most widely used strategies to fight cancer, although it has disadvantages such as accumulation in healthy organs and lack of specificity by cancer cells (non-targeted molecules), among others, resulting in adverse effects on patients that limit the dose or follow-up with the same. However, the treatment can also fail due to the resistance mechanisms that cancer cells have to these agents. Because of these limitations, smart drug delivery strategies have been developed to overcome treatment challenges. These smart drug strategies are made with the aim of passively or actively releasing the drug into the tumor environment, increasing the uptake of the chemotherapeutic agent by the cancer cells, thus reducing the adverse effects on other vital organs. Also, these strategies can be guided with molecules on their surface that interact with the tumor microenvironment or with specific receptors on the cancer cell membrane, thus conferring high affinity. This mini review summarizes advances in the development of drug delivery techniques for cancer treatment, including different smart nanocarriers with single or multifunctional stimuli responsiveness. At the same time, we highlight the toxicity and delivery of these strategies in in vivo models. Despite innovation in smart delivery techniques, there are still biodistribution and customization challenges to be overcome in future research.